Strengthening national character through multicultural-based civic education learning at Madrasah Ibtidaiyah - Ana Quthratun Nada; Istiningsih Istiningsih; Sri Sumarni; Hanif Faturrachim (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2026)
This study aims to analyze the internalization of national values through multicultural-based Civic Education learning in Madrasah Ibtidaiyah. This research employed a qualitative case study conducted in several public and private elementary schools in Sleman Regency, Special Region of Yogyakarta, Indonesia. The research participants consisted of Civic Education teachers, school principals, and fifth-grade students selected purposively, while informants were identified through snowball sampling until data saturation was reached. Data were collected via classroom observations, interviews, and documentation, and then analyzed using reduction, display, and conclusion techniques. Findings indicate that values such as love for the country, tolerance, and cooperation are taught through contextual and collaborative learning strategies, such as group discussions, reflective activities, and experiential learning. The role of teachers and school leadership is crucial in fostering an inclusive environment through supportive school programs and participatory learning practices. Students also exhibited positive changes, including respect for diverse opinions and collaboration with peers from different backgrounds. Despite challenges related to socio-cultural diversity and varying levels of awareness, strategies such as contextual learning, teacher guidance, and inclusive programs enhance multicultural education. Therefore, multicultural-based Civic Education in elementary schools is vital for promoting an inclusive national character and respect for diversity.